Administration of Customs Payments: International Standards for the Interaction of Tax and Customs Authorities - M. A. Ryl’skaya; S. O. Shokhin; O. G. Bobrova; A. Y. Kozhankov; N. V. Eremeeva (Финансы: теория и практика)
The authors have formulated and consistently proved the hypothesis that well-functioning interaction of tax and customs authorities is required to increase the effciency of the state revenues administration. The mechanism of this interaction should be formed when implementing the standards of the World Customs Organization and the World Trade Organization into the Russian legislation. The research is particularly relevant since Federal Law No. 289 of 03.08.2018 “On Customs Regulation” has entered into force. This law includes article 222 “Interaction and cooperation of customs and tax authorities”. As scientifc and practical results, promising areas for development have been worked out: improving unifed mechanism of customs, tax administration and currency control based on integrated innovative technologies; implementing international standards developed under the auspices of the World Customs Organization; creating prerequisites for the transition to the payment of import customs duties and taxes after the release of goods for law-abiding business; redistributing functions of customs and tax authorities. The authors propose to leave the control of import duties payments for the customs authorities, and to delegate the control of VAT and excise taxes on imported goods payments to the tax authorities. The article includes the results of a comparative legal analysis of the acts of the World Customs Organization, the Financial Action Task Force on Money Laundering (FATF), the Organization for Economic Cooperation and Development (OECD) and the Agreement on Cooperation of the Federal Customs Service and the Federal Tax Service of Russia. It justifes the conclusion that the studied cooperation is the most important tool for the customs payments administration. This is confrmed by the statistics on additional and pre-leased revenues to the state budget based on the results of joint and coordinated verifcation activities. The result of the study is the formulation of promising areas for improving the interaction of customs and tax authorities in the Eurasian Economic union (EAEu) and Russia.